ANALISIS PUTUSAN PENGADILAN NEGERI SORONG DALAM PERKARA TINDAK PIDANA PENISTAAN AGAMA MELALUI MEDIA SOSIAL: Studi Putusan Nomor 122/Pid Sus/2020/PN.Son - Aisyah, Pinasti (Prodi Hukum Keluarga (Akhwal Syahsiyyah) IAIN Sorong, 2024)
This research aims to determine the basic legal considerations of District Court Judges. Sorong Number 122/Pid.Sus/PN. Children in criminal cases of religious blasphemy through social media and the application of positive law to PN decisions. Sorong Number 122/Pid.Sus/2020/PN. Children in criminal cases of religious blasphemy via social media. The research used uses a Normative Juridical Approach. The types of data used are primary data and secondary data, namely data obtained through observation, interviews, literature study and documentation techniques. In analyzing data writing using qualitative descriptive analysis. The results of the research show that (1) Analysis of the Sorong District Court's Decision in the Case of the Crime of Blasphemy via Social Media (Decision Study Number 122/Pid.Sus/2020/PN.Son), that the Sorong District Court's Decision, in this case the Judge decided on the case not yet objective in seeing various points of view. so that the punishment for retaliation is completely irrelevant in its application. Legislation as a legal product is capable of being taken into consideration by judges in deciding a case, in accordance with the applicable laws and regulations in order to achieve legal certainty, benefit and provide the value of justice therein. In implementing positive law against PN decisions. Sorong Number 122/Pid.Sus/2020/PN. Son, in the case of the criminal act of blasphemy through social media, it was not appropriate for the judge to hand down a criminal decision against the defendant, based on the Criminal Code, the prison sentence in this case was 6 years, in the implementation of the law, he was only sentenced to 4 months, this is not relevant so that the public can judge that the consideration discriminatory judges and unfair disparities (differences in sentences). In the application of criminal justice, it must be in accordance with applicable laws and regulations, so that other people become wise in carrying out actions, so that they do not cause problems for themselves and others by expressing themselves to violate the law which triggers problems that can solve a religious group. certain people, who should respect and respect each other in their religious identity and the way they carry out their worship.